Economic Mechanism and Cash Flows Modeling for Reverse Mortgage - E. V. Kuz’mina; A. A. Yanin (Финансы: теория и практика, 2018)
The research is devoted to the economic mechanism of reverse mortgage —  a credit product aimed at improving the standard of living of senior citizens, owners of real estate. The idea of the reverse mortgage has been given, as well as the mechanisms of use of real estate owned by senior citizens in order to provide them with additional income. The examples of reverse mortgage in the uS, the uK, Spain and Australia have been given. The authors have also described the methods of reverse mortgage lending in Russia. Based on the analysis of international experience, the economic expediency of investing in this credit tool has been assessed. Considering consumer demand factor, it is possible to calculate the equilibrium rate and, therefore, to find the coordinates of the market equilibrium point. The authors have developed a mathematical model of reverse mortgage for the case of lifetime annuity payments. This model allows to calculate the expected benefits of borrowers and lenders. There have been done (and implemented) two notes that significantly distinguish reverse mortgage modeling from other loan products: 1) a lifetime reverse mortgage does not have a fixed expiration date; 2) when taking a loan of this type, borrowers consider not only consumption, but also accumulation of inheritance. The model allows to calculate the position of break-even points and market equilibrium (relative to the interest rate). This will help economically interested agents to assess the potential of the reverse mortgage market in Russia.